The constitutional court of Ukraine as an element of national mechanism for provision of criminal proceedings - Іванов , М. С. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2018)
The Constitutional Court of Ukraine has a special place in the system of judicial system and in the national mechanism of ensuring the rights of criminal proceedinds participants» and therefore has always been and remains the subject of lively scientific discussions among scholars and practitioners, that determines the relevance of this scientific research. The purpose of this research is a scientific analysis of the place and the role of the CCU in the national mechanism of ensuring the rights of participants in criminal proceedings, the definition of the correlation between the concepts of «constitutional jurisdiction» and «constitutional justice», the establishment of the main tasks implemented by the Constitutional Court in order to ensure the rights and freedoms of a man and a citizen, as participants of the criminal proceedings. The article defines the relation between concepts «constitutional jurisdiction» and «constitutional justice» and justifies that constitutional justice is an external form of constitutional jurisdiction, which is intended to ensure the independence and efficiency of constitutional jurisdiction in the performance of its tasks. Taking into account the reform processes that take place in Ukraine, including the introduction of a constitutional complaint institute, which is a direct manifestation of the functions of ensuring the rights of participants in criminal proceedings, there is an urgent need for a comprehensive scientific study of the Constitutional Court of Ukraine as an element of a national mechanism for ensuring the rights of participants in criminal proceedings. The research analyzes the scientific approaches to the tasks implemented by the Constitutional Court in order to ensure human rights, including those involved in criminal proceedings. The author has proved that the task of the Constitutional Court as a body of constitutional justice is the functioning of constitutional jurisdiction, whose activity consists in the implementation of constitutional control, the resolution of legal disputes relating to constitutional legal relations, and the exercise of influence on the legal reality in the state within the powers that constitutionality justice is provided by law.

Конституційний Суд України посідає особливе місце в системі судоустрою та національному механізмі забезпечення прав осіб, в тому числі учасників кримінального провадження, а тому завжди був і залишається предметом жвавих наукових дискусій серед науковців і практиків, що й обумовлює актуальність цього наукового дослідження. Метою статті є аналіз місця та ролі Конституційного Суду України у національному механізмі забезпечення прав учасників кримінального провадження. У статті визначено співвідношення понять «конституційна юрисдикція» та «конституційна юстиція» та обґрунтовано, що конституційна юстиція є зовнішньою формою конституційної юрисдикції, що покликана забезпечувати незалежність і ефективність конституційної юрисдикції у виконанні нею своїх завдань. Встановлено, що Конституційний Суд України бере участь у забезпеченні прав учасників кримінального провадження як національного механізму забезпечення прав учасників кримінального провадження, роль Конституційного Суду України у забезпеченні прав учасників кримінального провадження є дуже важливою і необхідною для реалізації принципів правової держави в Україні. Також визначено, що Конституційний Суд України як державний орган покликаний стояти на сторожі Конституції України, виступаючи міцним і дієвим гарантом прав людини в країні, що зумовлює необхідність діяльності Конституційного Суду України як національного механізму забезпечення прав учасників кримінального провадження. У дослідженні проаналізовано наукові підходи щодо завдань, які реалізує Конституційний Суд з метою забезпечення прав людини, в тому числі учасників кримінального провадження. Автором доведено, що завданням Конституційного Суду як органу конституційної юстиції є функціонування конституційної юрисдикції, діяльність якої полягає у здійсненні конституційного контролю, вирішенні правових спорів, що стосуються конституційних правовідносин, і здійсненні впливу на правову дійсність у державі у рамках повноважень, що надані конституційній юстиції законом.
КОНСТИТУЦІЙНИЙ СУД УКРАЇНИ ЯК ЕЛЕМЕНТ НАЦІОНАЛЬНОГО МЕХАНІЗМУ ЗАБЕЗПЕЧЕННЯ. ПРАВ УЧАСНИКІВ КРИМІНАЛЬНОГО ПРОВАДЖЕННЯ
Keywords: The Constitutional Court of Ukraine; constitutional jurisdiction; constitutional justice; national mechanism of ensuring human rights; ensuring rights of participants in criminal proceedings.; Конституційний Суд України; конституційна юрисдикція; конституційна юстиція; національний механізм забезпечення прав людини; забезпечення прав учасників кримінального провадження.